Analisis Penggunaan Aplikasi Majoo Pada Laporan Keuangan Sesuai SAK EMKM Studi Kasus: UMKM Pohara - Sagala, Margaretha Dorlan Olivia; Rahmadi, Rahmadi; Rahmatullah, Marwanto (Jurnal Pendidikan Indonesia, 2025)
Financial management limitations often present challenges for MSMEs, particularly due to the difficulty in understanding financial conditions and accurately measuring business performance. To address this issue, the Indonesian Accounting Standards (SAK) for MSMEs (Empowerment and Facility) are available to assist MSMEs in financial management. Furthermore, various free cloud-based accounting applications, such as the Majoo application, simplify financial recording. The Majoo application has been used by the Pohara MSME. This research employed a quantitative method with a case study approach. Data analysis was conducted through data reduction, data presentation, verification, and conclusion drawing. The results indicate that the Majoo application assists MSME financial management. It is hoped that this research will provide insights for MSMEs that have not yet used the Majoo application